The poet-hero in the work of Byron and Shelley - CALLAGHAN, MADELEINE (Anthem nineteenth-century series, 2019)
'The Poet-Hero in the Work of Byron and Shelley' explores the poetic heroism developed in Byron and Shelley's poetry and drama. The book traces how the heroism of the poet, as an idea, an ideal and an illusion, undergoes many different incarnations and definitions as both poets shape distinctive and changing conceptions of the hero throughout their careers.